2017
DOI: 10.1073/pnas.1700349114
|View full text |Cite
|
Sign up to set email alerts
|

Oogenesis and reproductive investment of Atlantic herring are functions of not only present but long-ago environmental influences as well

Abstract: Following general life history theory, immediate reproductive investment (egg mass × fecundity/body mass) in oviparous teleosts is a consequence of both present and past environmental influences. This clarification questions the frequent use of season-independent (general) fecundity formulas in marine fish recruitment studies based on body metrics only. Here we test the underlying assumption of no lag effect on gametogenesis in the planktivorous, determinate-fecundity Atlantic herring (Clupea harengus) display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 48 publications
(65 reference statements)
0
27
0
Order By: Relevance
“…In addition, species with very slow oocyte growth rates such as Greenland halibut ( Reinhardtius hippoglossoides , Pleuronectidae) must begin oocyte recruitment to SG in the reproductive cycle prior to the spawning season they are spawned (Kennedy et al., ). Oocyte recruitment to SG with a duration greater than a year is reported both for total spawners like the Norwegian spring‐spawning herring, C. harengus, (dos Santos Schmidt et al., ) and for batch spawning determinate spawners like the Northeast Arctic cod (Thorsen & Kjesbu, ) and results in the appearance of a new cohort of SG oocytes which is clearly distinguished from the current season's crop (Figure ). This may also explain the cortical alveoli oocytes observed on striped mullet and striped bass at the time of spawning.…”
Section: Future Recommendationsmentioning
confidence: 95%
See 2 more Smart Citations
“…In addition, species with very slow oocyte growth rates such as Greenland halibut ( Reinhardtius hippoglossoides , Pleuronectidae) must begin oocyte recruitment to SG in the reproductive cycle prior to the spawning season they are spawned (Kennedy et al., ). Oocyte recruitment to SG with a duration greater than a year is reported both for total spawners like the Norwegian spring‐spawning herring, C. harengus, (dos Santos Schmidt et al., ) and for batch spawning determinate spawners like the Northeast Arctic cod (Thorsen & Kjesbu, ) and results in the appearance of a new cohort of SG oocytes which is clearly distinguished from the current season's crop (Figure ). This may also explain the cortical alveoli oocytes observed on striped mullet and striped bass at the time of spawning.…”
Section: Future Recommendationsmentioning
confidence: 95%
“…Because few fished populations have demonstrated senescence, maximum reproductive age is often considered comparable to maximum age. In most fishes, the reproductive cycle occurs at the annual scale (Bye, 1984;Rideout, Rose, & Burton, 2005) and includes a phase during which gonads are developing, a spawning capable phase (synonymous with the spawning period), followed by a phase in which gonads regress, to eventually enter the regenerating phase, indicative of reproductive inactivity (Brown-Peterson, Wyanski, Saborido-Rey, Macewicz, & Lowerre-Barbieri, 2011). At the individual level, the reproductive period is defined as the time between the onset of recruitment to SG and the spawning of the last oocytes during a reproductive cycle.…”
Section: Temporal Dynamics Of Oocyte Recruitment and Oocyte Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Spring‐ and fall‐spawning Atlantic Herring in the Gulf of Maine and Georges Bank showed distinct oocyte development cycles, which are similar to the differences between Norwegian spring and summer spawners that initiate oocyte development at different times (dos Santos et al. ). In contrast, autumn‐ and winter‐spawning herring in the North Sea initiate oocyte development at the same time, with both development and down‐regulation occurring over a longer period in the latter, leading to fewer but larger eggs (van Damme et al.…”
Section: Discussionmentioning
confidence: 61%
“…Consequently, the composition and condition of the spawning stock likely play an important role for stock productivity and resilience (Hixon et al., ). Our analysis also showed that time lags between condition, fecundity and spawning success can be detected, confirming previous findings (dos Santos Schmidt et al., ). It remains to be explored whether simplified proxies such as spawner demographics or mean weight are sufficiently capable of capturing these dynamics or whether better measurements are necessary.…”
Section: Discussionmentioning
confidence: 99%